THE INFLUENCE OF PRODUCT QUALITY, PRICE, AND ELECTRONIC WORD OF MOUTH ON EMINA PRODUCT PURCHASE DECISIONS (Case Study on UNPAB Management Study Program Students Class of 2020) - Nita Salsabila; Annisa Sanny (RADJA PUBLIKA, 2024)
This study aims to test and find out more clearly